Social Disciplines and humanities in Engineering Training in the Context of the FSES 3++ - V. D. Vasilyeva (Moscow Polytechnic University, 2019)
The article discusses the role of social disciplines and humanities in new educational programmes of engineering training, updated in connection with the introduction of HE FSES 3++. The notion of "general cultural competencies" is no longer used in the new educational standards although the "universal competencies" of HE FSES 3++ still correlate with the indicators of general human culture. The article considers the possibilities of the development of universal competencies in approximate basic educational programmes taking the project in the educational direction of 03.09.01 "Computer science and computing" as an example. The importance of social disciplines and humanities to form universal competences is noted. These disciplines provide the continuity of the educational process of the younger generation. The article gives a brief summary of the content of the proposed social disciplines and humanities, describes the conditions for its variation, possible forms of learning activities that ensure the development of universal competencies of future engineers.